3. ELALUATION OF THE ROLE OF MULLER’S MANEUVER IN DIAGNOSING THE SITE OF UPPER AIRWAY OBSTRUCTION IN SLEEP APNEA/ SNORING SYNDROME (Vietnam Journal of Community Medicine, 2025)
apnea condition.Subjects and methods: The research involved 34 patients seeking surgical intervention for snoring at the National Otorhinolaryngology Hospital from January 2024 to September 2024.Results: Features of the upper airway obstruction's location: only 20.6% of cases with turbinate hypertrophy, 14.7% with deviated septum, 17.6% with long and broad uvula, 13.5% with hypertrophied tonsils at the base of the tongue, and 1 patient (2.9%) with grade 4 tonsil and Mallampati hypertrophy were found during regular otolaryngologist endoscopy. The soft palate, lateral pharyngeal wall, base of the tongue, and epiglottis all completely collapsed at 41.2%, 70.6%, 0%, and 2.9%, respectively, during the Muller maneuver.Conclusions: The Muller maneuver provides a basis for accurately diagnosing the location of airway narrowing causing snoring/sleep apnea and planning appropriate treatment, contributing to improving treatment quality.
Keywords: Muller’s maneuver; obstructive sleep apnea syndrome; snoring.